2004
DOI: 10.1007/s00425-003-1148-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a yeast-derived invertase in companion cells results in long-distance transport of a trisaccharide in an apoplastic loader and influences sucrose transport

Abstract: Companion cell-specific expression of a cytosolic invertase from yeast ( Saccharomyces cerevisiae) was used as a tool to synthesise oligosaccharides in the sieve element/companion cell complex and study whether oligosaccharides could be transported in the phloem of an apoplastically loading species. Potato ( Solanum tuberosum L.) plants expressing the invertase under the control of the Agrobacterium tumefaciens rolC promoter produced the trisaccharide 6-kestose in leaves, which was transported via the phloem a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…2X35S::AI-1) suggest that modest levels of heterologous invertase expression may be suYcient to alter the WT phenotype. These Wndings are not unique to this study as signiWcant diVerences in invertase activity were not detected in leaf mid ribs of Solanum tuberosum between a line expressing CI under the control of a companion cell-speciWc promoter (rolC invertase 3) and WT plants (Zuther et al 2004). Thus, it is plausible that the tissue-speciWc 4CL promoter and the 2X35S promoter lead to levels of heterologous invertase activity that are diYcult to detect above background activity of native invertase, yet allow suYcient expression to generate phenotypes that diVer from WT tobacco.…”
Section: Discussionmentioning
confidence: 76%
“…2X35S::AI-1) suggest that modest levels of heterologous invertase expression may be suYcient to alter the WT phenotype. These Wndings are not unique to this study as signiWcant diVerences in invertase activity were not detected in leaf mid ribs of Solanum tuberosum between a line expressing CI under the control of a companion cell-speciWc promoter (rolC invertase 3) and WT plants (Zuther et al 2004). Thus, it is plausible that the tissue-speciWc 4CL promoter and the 2X35S promoter lead to levels of heterologous invertase activity that are diYcult to detect above background activity of native invertase, yet allow suYcient expression to generate phenotypes that diVer from WT tobacco.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that overexpression of yeast invertase in the companion cell cytosol of potato results in the synthesis and transport of a novel trisaccharide, 6-kestose (Zuther et al, 2004). To test whether overexpression of cell wall invertase modifies the transport sugars in poplar, we analyzed sugars extracted from the petioles of leaves exposed to 14 CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…We are also grateful to Prof. Mark Tester, Australian Centre for Plant Functional Genomics, University of Adelaide, Australia, for discussing hydroponic growth of barley plants. Special thanks to Dr. Ellen Zuther, Max-Planck-Institute for Plant Molecular Physiology, Golm, Germany, for providing us with purified 6 kestose (Zuther et al, 2004) for peak identification. U.R.…”
Section: Acknowledgmentsmentioning
confidence: 99%